Keefektifan Model Discovery Learning Terhadap Aktivitas Dan Hasil Belajar Membaca Intensif Pada Siswa Kelas III UPT SD Negeri 2 Turatea Kabupaten Jeneponto - Devi Permatasari; Andi Adam; Muhammad Saeful (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research is motivated by the relatively low student achievement which is suspected because students are lazy to read and students are still difficult to understand the meaning of the text they read. Therefore it needs a strategy to be able to improve student learning outcomes. So one way that can be taken to improve this is by utilizing the Discovery Learning learning model. The purpose of this study was to determine the Effectiveness of the Discovery Learning Model on Students' Activities and Learning Outcomes of Intensive Reading in Grade III UPT SD Negeri 2 Turatea Jeneponto Regency. This type of research is a type of Pre Experimental Design research. The population in this study were students of class III UPT SD Negeri 2 Turatea and the sample in this study were some of the population of class III students of UPT SD Negeri 2 Turatea. The data collection method used is the observation method and the questionnaire method. The data analysis technique used is descriptive statistical analysis and inferential data analysis.From the results of the research it is known that the value of intensive reading learning results for third grade students at UPT SD Negeri 2 Turatea, Jeneponto Regency. This can be proven from the average student pretest result, which is 53.65, which is in the very low category, while the average student posttest result, which is 82.25, is in the high category. Strengthened by the results of the student intensive reading response questionnaire, it was effective because it met the student response questionnaire criteria, namely ≥ 75% gave a positive response.The results of the t test obtained tCount = 23.79 and tTable = 2.093, then tCount > tTable or 23.793 > 2.093 was obtained. So it can be concluded that H0 is rejected and H1 is accepted. This indicates that research using the discovery learning model can increase the activity and learning outcomes of intensive reading skills in class III UPT SD Negeri 2 Turatea, Jeneponto Regency.